2021
DOI: 10.52711/0974-360x.2021.00477
|View full text |Cite
|
Sign up to set email alerts
|

In vitro Antioxidant potential, Total Phenolic and Flavonoid contents in Justicia gendarussa leaf extracts

Abstract: Free radicals are triggered in human body by routine metabolic pathways which are highly reactive substance entangled in various physiological functions but excess production may impart with multitude diseases such as cancer, arthritis, inflammation and various neurodegenerative disorders. As a result, previous findings supported that various photochemical constituents present in natural plants exerts prominent role in defense mechanism against rate of excess free radicals’ production. The present study was ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…These results show that semi-polar ethanol extracts flavonoids from the leaves. Previous studies showed the best extraction of flavonoids fro m this plant using ethanol as a solvent (Kuber, 2021).…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…These results show that semi-polar ethanol extracts flavonoids from the leaves. Previous studies showed the best extraction of flavonoids fro m this plant using ethanol as a solvent (Kuber, 2021).…”
Section: Discussionmentioning
confidence: 93%
“…In this study, the antioxidant activity according to the DPPH method showed optima l results by extraction using a hexane solvent, while it is based on the FRAP method using a mixed solvent of ethanol and hexane. Previous studies using water, ethanol, ethyl acetate, and hexane solvents reported that the ethanolic extract of J. gendarussa had the best antioxidant activity (Kuber, 2021).…”
Section: Discussionmentioning
confidence: 96%
“…The leaves of J. gendarussa contain phenolics and flavonoids (Kuber 2021;Marliani et al 2022). Phenolics and flavonoids have important biological roles, such as plant growth regulation, defense mechanisms against pathogens and predators, plant pigmentation, protection from UV rays, and nitrogen fixation mechanisms.…”
Section: Introductionmentioning
confidence: 99%